Successful Typical AVNRT Ablation - Angela Bety Ratnasari; Budi Baktijasa Dharmadjati (Universitas Airlangga, 2022)
AVNRT is the most common regular arrhythmia in humans, and therefore the most commonly encountered during ablation attempts for regular tachycardias. Case Summary: We present a 41-year-old female patient with chest palpitations in the last 10 years, but prior to hospitalization felt heavy sensation on her chest and hospitalized due to heavy chest palpitations and documented SVT. She had no history of hypertension, diabetes mellitus, coronary heart conditions, or stroke. Physical examination showed fair general condition with GCS E4V5M6, blood pressure 130/80, pulse rate 96x / minute, breath rate 18 x / minute and saturation of 99%. Physical examinations are within normal limits. Discussion: Catheter ablation for AVNRT is the current treatment of choice in symptomatic patients. It reduces arrhythmia-related hospitalizations and costs, and substantially improves quality of life. Catheter ablation approaches aimed at the fast pathway have been abandoned; slow pathway ablation, using a combined anatomical and mapping approach, is now the method of choice. This approach offers a success rate of 95 %, has a recurrence rate of approximately 1.3 – 4.0 %, and has been associated with a low risk of atrioventricular (AV) block.